Implementing a Continuum of Evidence-Based Psychosocial Interventions for People with Severe Mental Illness: Part 1—Review of Major Initiatives and Implementation Strategies. (April 2014) - Menear, Matthew; Briand, Catherine
Objective: Providing comprehensive care to people with severe mental illness (SMI) involves moving beyond pharmacological treatment and ensuring access to a wide range of evidence-based psychosocial services. Numerous initiatives carried out in North America and internationally have promoted the widespread adoption of such services. Objectives of this rapid review were 3-fold: to identify these implementation initiatives, to describe the implementation strategies used to promote the uptake of psychosocial services, and to identify key issues related to the implementation of a broad range of services. Part 1 presents findings for objectives 1 and 2 of the review. Method: Searches were carried out in MEDLINE and PsycINFO for reports published between 1990 and 2012 using key words related to SMI, psychosocial practices, and implementation. Contacts with experts and reference list and reverse citation searches were also conducted. Results: Fifty-five articles were retained that identified more than a dozen major North American and international implementation initiatives. Initiative leaders employed diverse strategies at the planning, execution, and evaluation stages of the implementation process. Stakeholder meetings, training, ongoing consultation, and quality or fidelity monitoring were strategies consistently adopted across most initiatives, whereas theory-based approaches and organizational- and system-level strategies were less frequently described. Conclusion: Insights from the initiatives identified in this review can help guide future efforts to implement a broad range of psychosocial services for people with SMI. However, such efforts will also need to be informed by more rigorous, theory-based studies of implementation processes and outcomes.